Macromol. Chem. Phys. 4/2018. Issue 4 (19th February 2018) - Peng, Fei; Qiu, Liang; Chai, Ran; Meng, Fanfan; Yan, Chunmei; Chen, Yulan; Qi, Junjie; Zhan, Yong; Xing, Chengfen
Abstract : Front Cover : Folic‐acid‐modified conjugated polymer nanoparticles (FA‐CPNs) are exploited to target cancer cells and destroy the neighboring cancer cells. FA‐CPNs produce cytotoxic reactive oxygen species upon irradiation by 600 nm light, causing the cell death of folate‐receptor‐overexpressed cancer cells. Therefore, the conjugated polymer‐based nanoparticles provide a multifunctional system for targeting cancer cells and photodynamic therapy. Further details can be found in article number1700440 by Yulan Chen, Chengfen Xing, and co‐workers.